Gut Microbiome and the Role of Metabolites in the Study of Graves’ Disease - Liu, Haihua; Liu, Huiying; Liu, Chang; Shang, Mengxue; Wei, Tianfu; Yin, Peiyuan (Frontiers in Molecular Biosciences, 2022)
Graves’ disease (GD) is an autoimmune thyroid disease (AITD), which is one of the most common organ-specific autoimmune disorders with an increasing prevalence worldwide. But the etiology of GD is still unclear. A growing number of studies show correlations between gut microbiota and GD. The dysbiosis of gut microbiota may be the reason for the development of GD by modulating the immune system. Metabolites act as mediators or modulators between gut microbiota and the thyroid. The purpose of this review is to summarize the correlations between gut microbiota, microbial metabolites and GD. Challenges in the future study are also discussed. The combination of microbiome and metabolome may provide new insight for the study and put forward the diagnosis, treatment, prevention of GD in the future.